Heavy metal distribution in wheat plant components following foliar Cd application. (May 2023) - Liu, Pengkun; Li, Liping; Ippolito, James A.; Xing, Weiqin; Wang, Yali; Wang, Yale; Cheng, Yongxia; Qiu, Kunyan
Abstract: Atmospheric deposition of Cd, from anthropogenic activities, can be directly deposited onto and absorbed into wheat plants, yet, how foliar absorbed Cd is translocated in wheat plants is not well understood. A pot experiment investigated foliar Cd application on the accumulation and distribution of heavy metals in various wheat parts. Wheat was grown in a Cd/heavy metal contaminated soil, and from grain heading to the filling stage, 0, 10, 20, 30 and 40 mg kg −1 Cd solution was sprayed repeatedly on leaves (grain heads were covered). Foliar Cd application had no effect on grain yield and Cd concentration (3.01–3.51 mg kg −1 for all treatments), while increased flag leaf blade and sheath Cd concentrations by 1.06–2.77 and 0.00–0.66 times, respectively. Cadmium concentration in the center of the peduncle, from the 40 mg kg −1 Cd solution treatment, was 1.41 times that of the control (10.3 vs 7.30 mg kg −1 ). Foliar Cd application also increased Cd accumulation (concentration × mass) of the flag leaf blade and sheath. Rachis and grain Pb concentrations were reduced, while stem Pb concentration was increased by Cd application. Cadmium application negatively affected whole plant Ni accumulation and concentration of certain wheat parts; Ni absorption inhibition may have occurred in roots via the downward transport of Cd. Overall results implied that the predominant portion of foliar applied Cd was retained in leaves, while lesser portions migrated to peduncle or root and affected the absorption/distribution of other metals in wheat plants. These results are important for further discerning the mechanism of wheat grain Cd accumulation, especially when grain is raised in areas where atmospheric deposition of Cd (e.g., near smelting facilities) is an issue from an environmental and human health perspective. Graphical abstract: Image 1 Highlights: Approximately 83% of the foliar absorbed Cd was retained in wheat leaves. Leaf Cd had low mobility, whether absorbed via shoot or root. Foliar absorbed Cd affected metal accumulation in wheat grain and plant components. A portion of foliar absorbed Cd translocated to roots, inhibiting root Ni absorption.